Comparative politics - Caramani, Daniele (Oxford University Press, 2023)
From the very first edition of this textbook on Comparative Politics, the ambition was to produce an exciting, authoritative, and up-to-date teaching instrument. We have tried to write chapters of the highest standard in terms of their content, with comparative information supported by cutting-edge theories and rigorous methodology. We aimed to provide comprehensive chapters in their substantive coverage of the field, and a worldwide range of countries. We hope that the sixth edition will speak to comparative politics students at all levels, as well as to lecturers who will use it for their classes, as did the previous five editions. Our goal is an integrated text with a maximum of cross-references between chapters. At the same time, the modular structure with self-contained chapters should maximize its appeal to lecturers and students, alongside accessible language enhanced by a number of learning features and a similar format throughout. This structure does not require that it be read cover to cover. The book can be used in any order, making it possible to compose courses with a 'variable geometry'. For the same reason, more but shorter chapters have been preferred.